БИОФИЗИЧЕСКИЕ ПРЕДВЕСТНИКИ ЗЕМЛЕТРЯСЕНИЙ, ПЕРСПЕКТИВЫ АНТИСЕЙСМИЧЕСКОЙ ЗАЩИТЫ (Experimental biology, 2015)
Bioplasma reflects dynamics of processes and fluctuation in geoplasma as well as in lithosphere and hydrosphere hydroplasma. For 30 years of researches the databank of biophysical premonitory symptoms of earthquakes is collected that makes possible to carry out the intermediate term, short-term and operative prediction of earthquakes for Almatyand southern regions of Almaty area. The system of neutralization of seismic activity in points of its maximum evidence (soliton in geoplasma) for aseismic protection of Almaty, high-rise dams (Buhtarminskiy, Sajano-Shushenskaya Hydroelectric power station, the atomic power station, etc.) is offered.
Keywords: Bioplasma; soliton in geoplasma